Thyroid Disorders Focus on Hyperthyroidism - Diaz Soto, Gonzalo (IntechOpen, 2014)
The thyroid disorders are one of the most common and exciting areas of endocrinology. Hypothyroidism, multinodular goiter, hyperthyroidism and thyroid cancer are only few of the several implications that the thyroid disorders have in health. In fact, thyroid hormones regulate not only metabolism process, but also many other molecular and physiological systems. From this point of view, hyperthyroidism complications are a good example of the significance of thyroid hormone actions. This book aims to provide a general view of thyroid disorders, and a deeper explanation of hyperthyroidism and its complications and impact in health.